Consumer Choice and Data Envelopment Analysis: The Case of Discrimination on Housing Markets - Bernd Ebersberger; Uwe Cantner; Horst Hanusch (Universität Augsburg, Institut für Volkswirtschaftslehre, 1997)
The objective of this paper is twofold. First we discuss, whether data envelopment analysis can be applied to households' consumption activities on the basis of Kelvin Lancaster's approach to consumer choice. Then, we apply data envelopment analysis to identify inefficiencies in a subsector of the Augsburg (Germany) housing market. These inefficiencies can be attributed to differential treatment by landlords. With these inefficiencies occuring systematically for certain householdtypes we conclude that discriminatory behavior exists.
urn:nbn:de:bvb:384-opus4-243542
Keywords: 330